Profiles and Geotechnical Properties for some Basra Soils - Al-Taie, Abbas J. (Al-Khwarizmi Engineering Journal, 2015)
Abstract Basra province is known for its logistic location for trading activity and oil industry. By geological point of view, Basra areas are believed to consist mainly of alternation of (clay, silty clay, clayey silt, silt and sand) type of soil. Any development of industry in this area should be affected by the occurrence of the clay soil. That is why the investigation to the soil is more than necessary. In this case, a vast testing program was carried out by the author to evaluate the various formations constituting the of some Basra soils. An attempt to characterize and discuss the nature, minerals, engineering behavior and field properties of soil samples extracted from more than one thousand and one hundred boring liner meters of three sites was performed. The average values of various geotechnical design properties are calculated and plotted with depth. A preview of climate, geology, seismicity and earthquakes of the study area was conducted. Finally, the typical soil profiles were prepared. Keywords: Basra soil, soft clay, lean clay, Atterberg limits, moisture content, shear strength, standard penetration,